Pemanfaatan Media Gambar dalam Meningkatkan Keterampilan Berbahasa Pemelajar BIPA - Syakir, Akhmad; Istiqamah, Istiqamah; Leha, Noor; Daviria, Eqmi Avi; Fitri, Diani; Putri, Diani (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Teaching Indonesian to Speakers of Other Languages (BIPA) requires continuous innovation to maintain motivation and increase the active participation of learners. This community service activity aims to introduce and implement the use of two interactive media, namely "Self-Introduction" and "Mysterious Envelope," to BIPA instructors. The implementation method consists of three stages, including (1) an explanation of interactive learning concepts, (2) a demonstration and simulation of the use of both media, and (3) a direct practice session by the participants of the technical guidance program. The results of the activity showed very high enthusiasm from the instructors. The "Self-Introduction" and "Mysterious Envelope" media were considered highly relevant, practical, easy to replicate, and capable of creating a dynamic and enjoyable learning atmosphere. The participants were able to practice using the media directly and provided positive feedback regarding the potential for its application. It is concluded that the development and dissemination of interactive media through partnerships with professional organizations such as APPBIPA is an effective strategy for enhancing the pedagogical competence of instructors and the quality of BIPA learning on a broader scale.